2006
DOI: 10.1364/ol.31.003414
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive long-period fiber-grating strain sensor with low temperature sensitivity

Abstract: A long-period fiber-grating sensor with a high strain sensitivity of -7.6 pm/microepsilon and a low temperature sensitivity of 3.91 pm/ degrees C is fabricated by use of focused CO(2) laser beam to carve periodic grooves on a large- mode-area photonic crystal fiber. Such a strain sensor can effectively reduce the cross-sensitivity between strain and temperature, and the temperature-induced strain error obtained is only 0.5 microepsilon/ degrees C without using temperature compensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
146
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(152 citation statements)
references
References 8 publications
3
146
0
3
Order By: Relevance
“…12,86,87 In contrast, CO 2 laser irradiation is a highly efficient, low cost technique for writing a LPFG in a pure-silica PCF without photosensitivity. 20,24,25,27 Kakarantzas et al 20,88 reported, as shown in Fig. 5, the first example of structural LPFGs written in pure-silica solidcore PCFs.…”
Section: B To Write Lpfgs In Solid-core Pcfsmentioning
confidence: 96%
See 3 more Smart Citations
“…12,86,87 In contrast, CO 2 laser irradiation is a highly efficient, low cost technique for writing a LPFG in a pure-silica PCF without photosensitivity. 20,24,25,27 Kakarantzas et al 20,88 reported, as shown in Fig. 5, the first example of structural LPFGs written in pure-silica solidcore PCFs.…”
Section: B To Write Lpfgs In Solid-core Pcfsmentioning
confidence: 96%
“…6, an asymmetrical LPFG with periodic grooves was written in a pure-silica large-mode-area PCF by the use of a focused CO 2 laser beam. 24,25 The repeated scanning of the focused CO 2 laser beam creates a local high temperature in the fiber, which leads to the collapse of air holes and the gasification of SiO 2 on the fiber surface. Consequently, periodic grooves with a depth of about 10 m and a width of about 60 m are created on the fiber, as shown in Fig.…”
Section: B To Write Lpfgs In Solid-core Pcfsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since Davis et al reported the first CO 2 -laserinduced long period fiber grating (LPFG) in a conventional glass fiber in 1998 [1], various CO 2 laser irradiation techniques have been demonstrated and improved to write high-quality LPFGs in different types of optical fibers such as conventional glass fibers [2,3], solid-core photonic crystal fibers [4,5], and air-core photonic bandgap fibers [6]. The enhancement of the grating-writing efficiency is critical to achieving a high-quality LPFG with desired mode-coupling efficiency.…”
Section: Introductionmentioning
confidence: 99%